REPRESENTATION OF NOSTALGIA IN THE PROGRAM MEMORI MELODI IN TVRI NASIONAL - Ramadhoni, Ayudha Eka; Sugihartono, Ranang Agung (Seni Media Rekam ISI Surakarta, 2020)
This study describes the representation of nostalgia in the “Memori Melodi” music program in the episode Tribute To Yon Koeswoyo. This study uses a construction approach from the representation of Stuart Hall. The sampling technique uses purposive sampling technique. Data collection used is observation without a roleplay and interviews. Data analysis used Miles and Huberman model data analysis which consisted of data reduction, data presentation, conclusion drawing and verification. The results of this study indicate there is a nostalgic representation in the music program of “Memori Melodi” episode Tribute To Yon Koeswoyo. The appearance of nostalgic is constructed through verbal and non-verbal language in each segment. The construction of social interactions between the performers (host, singer, audience) and sensory input (music, visual, narrative about Koes Plus and Yon Koeswoyo, and expressions of the performers) is a form of nostalgia in the Tribute To Yon Koeswoyo's episode. This nostalgic representation is useful knowledge about the reappearance of nostalgia in music programs on television.